The milk of human kindness: the story of the Mothers Milk Bank at Austin - Wilson-Clay Barbara (BMC, 2006)
Abstract Increased scientific study of human milk and awareness of the special nutritional needs of the premature infant have stimulated interest in human donor milk banking. Yet only three donor human milk banks existed in the United States in 1998. Having observed better outcomes in human milk-fed neonatal intensive care patients, two neonatologists in Austin, Texas, founded The Mothers Milk Bank at Austin (MMBA). Since opening in 1999, the MMBA has expanded rapidly as the result of careful planning, innovative procedures, fiscal stability, and widespread community support. The non-profit organizational structure, diversity and progressive vision of the board of directors and staff, and creative on-going public relations efforts have contributed to the success of the project. The MMBA demonstrates a model for 21st century milk banking.